PHYSICAL EDUCATION AND ITS BASICS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
It is necessary to determine the correlation between the integral dimensions of technical skill, the rhythm-tempo system and the data of special physical training. The rhythm will reflect the stresses being spent, depending on their value, time spent, and other characteristics of movement.